Determining the effective dose of esketamine combined with propofol for painless hysteroscopy: a prospective dose-finding study - Sheng, Zhimin; Liu, Xiang; Lin, Kang; Liu, Jie; Mao, Junqin; Qian, Xiaowei (Frontiers in Pharmacology, 2024)
BackgroundThe combination of esketamine and propofol has become a common choice for total intravenous anesthesia in hysteroscopic procedures. However, the optimal effective dose has not yet been determined. The aim of this study was to determine the median effective dose (ED50) and 95% effective dose (ED95) of esketamine compounded with propofol for painless hysteroscopy.MethodsA total of 40 patients aged 20–60 years and scheduled for painless hysteroscopy under intravenous anesthesia were recruited, and a total of 31 patients were enrolled for the final analysis. Using the Dixon’s up and down method, an initial dose of 0.5 mg/kg esketamine was administered intravenously before surgery, and after 1 min, it was followed by 2 mg/kg of propofol. If the hysteroscopy failed (a positive reaction) [defined as inadequate cervical dilatation, patient body movements interfering with surgical procedures during hysteroscopy placement, frowning, or Ramsay Sedation Scale (RSS) score <5 within 5 min], the subsequent patient’s esketamine dosage was increased by 0.1 mg/kg. Conversely (a negative reaction), the dosage was decreased by 0.1 mg/kg. The test was not stopped until at least 7 crossovers occurred. The perioperative adverse events of each patient were recorded. The ED50 and ED95 with 95% confidence intervals (CIs) were estimated using probit regression.ResultsThe ED50 and ED95 with 95% (CIs) of esketamine in patients were 0.287 (0.220–0.342) mg/kg and 0.429 (0.365–0.705) mg/kg, respectively. No serious adverse events were observed in any patients.ConclusionA dose of 0.429 mg/kg esketamine combined with propofol is recommended for painless hysteroscopy anesthesia, as it enhances anesthesia and postoperative analgesia efficacy without significant adverse reactions. However, potential risks associated with this dosage should be carefully considered in clinical practice.Clinical Trial Registrationhttps://www.chictr.org.cn/index.html, identifier ChiCTR2300075564.